Implementasi Etika Bisnis Islam dan Transformasi Digital UMKM Madura dalam Mendukung Ketercapaian Sustainable Development Goals - Nasrulloh Nasrulloh (JES (Jurnal Ekonomi Syariah), 2022)
This study aims at capturing the types of MSMEs in Madura; identifying the suitability of sharia business ethics of MSMEs in Madura; and describing the marketing management of MSMEs in Madura for increasing sales value and competitiveness in the digital economy industry so that they are able to support the achievement of the Sustainable Development Goals (SDG’s). Using a qualitative method with a literature study approach and in-depth interviews in field studies, the results of the study show that, in general, the portrait of MSME subject in Madura deals with the food industry of agricultural and marine products, herbal drinks and traditional herbs, as well as the wood carving manufacturing industry. and shipbuilding. As a society that has a high level of religiosity, some MSME subjects in Madura have implemented Islamic business ethics by processing halal certificates for their products. In order to increase marketing and sales of their products, they are familiar with the use of online marketplaces. They prefer to market their products offline or use personal social media and e-commerce accounts but are reluctant to join websites managed by the government. Changes in mindset and innovation, strengthening cooperation between parties and utilizing technological advances are strongly needed for the development and progress of MSME products in Madura. So that they are able to reach the global community and support the achievement of the Sustainable Development Goals (SDG’s).